Changes in Aggregation in a Conjugated Polyelectrolyte. (17th August 2015) - Keum, Sangha; Song, Suhee; Park, Seong Soo; Lee, Gun‐Dae; Suh, Hongsuk; Hyun, Myung Ho; Jin, Youngeup
<x xml:space="preserve">Abstract</x> <boxed-text content-type="graphic" id="bkcs10427-blkfxd-0001" position="anchor" orientation="portrait"> </boxed-text>